The Effect of State Minimum Wage Increases on CEO Compensation: Evidence of Labor Donation in Nonprofit Organizations - Balsam, Steven; Mao, Connie X.; Xu, Min; Zhang, Yinge (The Accounting Review, 2025)
ABSTRACT In this paper, we test the “labor donation” hypothesis, which posits that intrinsically motivated individuals willingly accept lower compensation to work in nonprofit organizations (NPOs). We do so by examining the response of NPO CEO compensation to exogeneous increases in labor costs resulting from state-level minimum wage hikes, finding these increases are followed by declines in CEO compensation. Consistent with the labor donation hypothesis, we find the declines in compensation are larger for CEOs who we expect to have greater intrinsic motivation, i.e., those whose NPOs are headquartered in counties with higher levels of religiosity, in counties with greater levels of social capital, and those who work for a local NPO as opposed to a national NPO. In contrast to the decline in compensation we observe for NPO CEOs, we do not find an impact on for-profit CEO compensation. JEL Classifications: G3; J33; J38; L3; L3.